A novel peptide from the skin of amphibian Rana limnocharis with potency to promote skin wound repair. Issue 20 (23rd September 2021) - Wang, Siyuan; Feng, Chengan; Yin, Saige; Feng, Zhuo; Tang, Jing; Liu, Naixin; Yang, Fu; Yang, Xinwang; Wang, Ying
Abstract: In clinical trials, the healing of wounds remains a substantial physiological and financial incumbrance on patients. Therefore, the development of new drugs that can accelerate wound healing is vital. Based on genomic methods, we identified a new peptide (RL-RL10) with the amino acid sequence 'RLFKCWKKDS' from the skin of an amphibian frog species ( Rana limnocharis ). RL-RL10 promoted wound healing of human keratinocytes (HaCaT) in a concentration-dependent manner. RL-RL10 also had an effect on the migration and proliferation of HaCaT cells and promoted healing of a full-thickness wound in mice in a dose-dependent manner. In conclusion, we discovered RL-RL10 that promoted healing activity of cellular and animal wounds, thus providing a new peptide template for the development of novel wound-repairing drugs. Graphical Abstract: